Targeting CD33+ acute myeloid leukemia with GLK-33, a lintuzumab-auristatin conjugate with a wide therapeutic window - Satomaa, Tero (American Association for Cancer Research, 2025)
CD33 (Siglec-3) is a cell surface receptor expressed in approximately 90% of AML blasts, making it an attractive target for therapy of acute myeloid leukemia (AML). While previous CD33-targeting antibody-drug conjugates (ADCs) like gemtuzumab ozogamicin (GO, Mylotarg) have shown efficacy in AML treatment, they have suffered from toxicity and narrow therapeutic window. This study aimed to develop a novel ADC with improved tolerability and a wider therapeutic window. GLK-33 consists of the anti-CD33 antibody lintuzumab and eight mavg-MMAU auristatin linker-payloads per antibody. The experimental methods included testing in cell cultures, patient-derived samples, mouse xenograft models, and rat toxicology studies. GLK-33 exhibited remarkable efficacy in reducing cell viability within CD33-positive leukemia cell lines and primary AML samples. Notably, GLK-33 demonstrated anti-tumor activity at single dose as low as 300 µg/kg in mice, while maintaining tolerability at single dose of 20 - 30 mg/kg in rats. In contrast to both GO and lintuzumab vedotin, GLK-33 exhibited a wide therapeutic window and activity against multidrug-resistant cells. The development of GLK-33 addresses the limitations of previous ADCs, offering a wider therapeutic window, improved tolerability, and activity against drug-resistant leukemia cells. These findings encourage further exploration of GLK-33 in AML through clinical trials.